Biocomplex textile as an alternative daily cover for the simultaneous mitigation of methane and malodorous compounds. (February 2018) - Choi, Hyungjoo; Ryu, Hee Wook; Cho, Kyung-Suk
Highlights: Biocomplex textiles were proposed as alternative daily covers in landfills. The textiles were made by inserting inorganic biocarriers between nonwoven fabrics. The mixture of perlite and tobermolite was the best biocarrier. The textiles maintained their activity after 70 days of storage. The textiles recovered their activity within 2–3 d after 17 d of starvation. Abstract: Space-saving biocomplex textiles, which can be used as covers or rolled up as needed, have been demonstrated as alternative daily covers for the simultaneous mitigation of greenhouse gases (GHGs) and odors in landfills. The biocomplex textiles were made by inserting inorganic biocarriers (perlite (P), tobermolite (T) and their mixture (P/T)) between nonwoven fabrics. Methane (CH4 ) and dimethyl sulfide (DMS) were used as model compounds for GHGs and odors, and a CH4 and DMS co-degrading microbial consortium was used as an inoculum source. CH4 and DMS could be biologically degraded by methanotrophs and sulfur-oxidizing bacteria in the biocomplex textiles. Both biocomplex textiles made with either P or T were able to maintain the removability for CH4 and DMS after storage for 70 days, although their removal efficiencies for CH4 and DMS were 70–71% and 62–65% of those before storage, respectively. CH4 and DMS were simultaneously removed in lab-scale landfill simulation reactors employed with the biocomplex textiles. After 17 days of starvation, only 2–3 days were needed to recover their removability. Among the 3 kinds of biocarriers evaluated, the biocomplex textile generated using the P/T showed the highest removability and was the most stable. The maximum elimination capacities of the biocomplex textile generated with the P/T were 11.5 g-CH4 ·m −2 -fabric·d −1 and 0.5 g-DMS·m −2 -fabric·d −1, respectively. These results suggest that the biocomplex textiles are promising alternative daily covers to mitigate the emission of greenhouse gas and odor in operational landfills.